Head‐to‐head comparison of amplified plasmonic exosome Aβ42 platform and single‐molecule array immunoassay in a memory clinic cohort. (23rd January 2021) - Tanaka, Tomotaka; Ruifen, Joyce Chong; Nai, Ying‐Hwey; Tan, Chin Hong; Lim, Carine Z. J.; Zhang, Yan; Stephenson, Mary C.; Hilal, Saima; Saridin, Francis N.; Gyanwali, Bibek; Villaraza, Steven; Robins, Edward G.; et al.
Abstract: Background and purpose: Various blood biomarkers reflecting brain amyloid‐β (Aβ) load have recently been proposed with promising results. However, to date, no comparative study amongst blood biomarkers has been reported. Our objective was to examine the diagnostic performance and cost effectiveness of three blood biomarkers on the same cohort. Methods: Using the same cohort ( n = 68), the performances of the single‐molecule array (Simoa) Aβ40, Aβ42, Aβ42/Aβ40 and the amplified plasmonic exosome (APEX) Aβ42 blood biomarkers were compared using amyloid positron emission tomography (PET) as the reference standard. The extent to which these blood tests can reduce the recruitment cost of clinical trials was also determined by identifying amyloid positive (Aβ+) participants. Results: Compared to Simoa biomarkers, APEX‐Aβ42 showed significantly higher correlations with amyloid PET retention values and excellent diagnostic performance (sensitivity 100%, specificity 93.3%, area under the curve 0.995). When utilized for clinical trial recruitment, our simulation showed that pre‐screening with blood biomarkers followed by a confirmatory amyloid PET imaging would roughly half the cost (56.8% reduction for APEX‐Aβ42 and 48.6% for Simoa‐Aβ42/Aβ40) compared to the situation where only PET imaging is used. Moreover, with 100% sensitivity, APEX‐Aβ42 pre‐screening does not increase the required number of initial participants. Conclusions: With its high diagnostic performance, APEX is an ideal candidate for Aβ+ subject identification, monitoring and primary care screening, and could efficiently enrich clinical trials with Aβ+ participants whilst halving recruitment costs. Abstract : Amplified plasmonic exosome (APEX) Aβ42 and single‐molecule array (Simoa) Aβ42/Aβ42 can efficiently enrich clinical trials with amyloid positive (Aβ+) participants whilst halving recruitment cost. With its good diagnostic performance, APEX is the ideal candidate for Aβ+ subject identification and monitoring and for primary care screening.